Selecting Infants With Cryptorchidism and High Risk of Infertility for Optional Adjuvant Hormonal Therapy and Cryopreservation of Germ Cells: Experience From a Pilot Study - Thorup, Jorgen; Clasen-Linde, Erik; Dong, Lihua; Hildorf, Simone; Kristensen, Stine Gry; Andersen, Claus Yding; Cortes, Dina (Frontiers in Endocrinology, 2018)
Introduction: Orchiopexy for congenital cryptorchid testes is recommended between ½ - 1 year of age to preserve testicular germ cell maturation. Early operation is not enough to preserve fertility in 22% - 36% of cases. Aim of study was to set up a protocol for optional adjuvant hormonal therapy after orchiopexy and thereafter cryopreservation of testicular biopsies from infants with bilateral cryptorchidism and high infertility risk. Material & Methods: We included seventeen boys with bilateral cryptorchidism, normal FSH and impaired Germ Cell Number per Tubular transverse Section (G/T) in testicular biopsies at orchiopexy, 7 months - 3½ years old. Postoperatively, optional adjuvant LHRH (Kryptocur®) 0.2mg/0.1ml x2 every second day in 16 weeks were offered. Ten boys were applicable for age-matching according to parent’s choice of treatment-regime and G/T. Five of them had kryptocur® and five were controls. Repeat bilateral testicular biopsy evaluation and cryopreservation were offered to all boys 12 months after primary orchiopexy. For cryopreservation tissue pieces were incubated with a cryoprotectant with a slow programme freezing. Results: Two out of 5 kryptorcur®-treated boys normalized both the average G/T and the number of adult dark spermatogonia (Ad-S). Another kryptocur®-treated boy with initial low G/T and no Ad-S increased the G/T and achieved normal number of Ad-S at time of cryopreservation. In the control group 2 patients reached only normal lower range regarding the G/T and the number of Ad-S. None of boys with less than average 0.2 G/T improved significantly, whether they were kryptocur®-treated or not. Conclusion: Based on literature and the present results we recommend adjuvant LHRH treatment to boys with cryptorchidism and insufficient genuine gonadotropin stimulation at time of surgery, as these patients have high infertility risk. Cryopreservation should be an option in case of treatment failure of adjuvant LHRH. However, in order to avoid repeat surgery with biopsy, some parents may choose biopsy for cryopreservation at time of the initial bilateral orchiopexy, well informed that the procedure may only be truly indicated in 22% - 36% of the cases.